Numerical model in water quality: The case study of Da Nang City in central Vietnam - Doan Thuy Kim Phuong; Vo Ngoc Duong; Nguyen Trung Quan; Nguyen Cong Phong; Doan Thi Ngoc Canh (River)
Abstract The planning and treatment of wastewater discharged into rivers and seas is vital for tourism, domestic water supply, and other key sectors. This study used the MIKE 21 model to evaluate water quality trends and the assimilative capacity of the Vu Gia River estuary and the major reservoirs in Da Nang, considering future pollution loads and climate change scenarios (RCP8.5). Key parameters assessed include DO, BOD₅, COD, and Coliform. Results show a general decline in water quality (WQI) from 2019 to 2030 and again by 2070, with DO and BOD₅ contributing most to pollution. While COD and Coliform remained within acceptable limits (WQI > 75), the Phu Loc River had the lowest WQI (66.0–62.2). Other affected areas include the Han River (downstream and upstream) and the Cu De River. Reservoirs like Dong Nghe and Hoa Trung maintained better water quality (WQI > 80), though a downward trend was still observed.